2019
DOI: 10.3390/microorganisms8010041
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Metals from Acid Mine Drainage by Bioelectrochemical System Inoculated with a Novel Exoelectrogen, Pseudomonas sp. E8

Abstract: Acid mine drainage (AMD) is a typical source of environmental pollution ascribing to its characteristics of high acidity and heavy metal content. Currently, most strategies for AMD treatment merely focus on metal removal rather than metal recovery. However, bioelectrochemical system (BES) is a promising technology to simultaneously remove and recover metal ions from AMD. In this study, both cupric ion and cadmium ion in simulated AMD were effectively recovered by BES inoculated with a novel exoelectrogen, Pseu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Understanding this behavior will be important for enabling accurate predictions of the geochemical reactivity underlying various geological and environmental technologies. For example, the inhibition of calcite dissolution by dissolved metal cations would negatively impact the efficiency of passive remediation of mine tailings and acid mine drainages where limestone (up to 95% calcite) is used to buffer acidic waters typically characterized by elevated levels of dissolved metals. Specifically, the inhibited dissolution of calcite could lead to a higher-than-expected mobility of contaminants under conditions where acid mine waters pass through limestone beds. A robust understanding of these metal–carbonate interactions would help in the development of more efficient remediation strategies for metal contaminants associated with mining activities.…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…Understanding this behavior will be important for enabling accurate predictions of the geochemical reactivity underlying various geological and environmental technologies. For example, the inhibition of calcite dissolution by dissolved metal cations would negatively impact the efficiency of passive remediation of mine tailings and acid mine drainages where limestone (up to 95% calcite) is used to buffer acidic waters typically characterized by elevated levels of dissolved metals. Specifically, the inhibited dissolution of calcite could lead to a higher-than-expected mobility of contaminants under conditions where acid mine waters pass through limestone beds. A robust understanding of these metal–carbonate interactions would help in the development of more efficient remediation strategies for metal contaminants associated with mining activities.…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…Cr(VI) To date, many reports have shown that the metal ion removal efficiency and electricity production performance in MFCs are mainly affected by the metal ion type and concentration, electrode materials, anode substrates, and microbe community [19,20]. It is very meaningful to better understand these factors and their effects on the system in order to develop efficient and applicable technologies for metal-polluted wastewater treatment.…”
Section: Typical Ions Reactions Stanmentioning
confidence: 99%
“…Ai et al . ( 2020 ) achieved the selective recovery of Cu, Cd and Fe by working under MFC or MEC mode, and Leon‐Fernandez et al . ( 2021 ) the sequential recovery of Cu (in MFC mode) and Sn, Ni and Fe (in MEC mode), also from simulated acid mine drainages (Ai et al ., 2020 ; Leon‐Fernandez et al ., 2021 ).…”
Section: Generation Iii: Electrified Biological Treatmentmentioning
confidence: 99%
“…( 2020 ) achieved the selective recovery of Cu, Cd and Fe by working under MFC or MEC mode, and Leon‐Fernandez et al . ( 2021 ) the sequential recovery of Cu (in MFC mode) and Sn, Ni and Fe (in MEC mode), also from simulated acid mine drainages (Ai et al ., 2020 ; Leon‐Fernandez et al ., 2021 ). Finally, other studies have reported the coupling of bioanodes with the cathodic metal removal by precipitation as metal hydroxides or carbonates (Lefebvre et al ., 2012 ; Colantonio and Kim, 2016 ).…”
Section: Generation Iii: Electrified Biological Treatmentmentioning
confidence: 99%